Pengembangan Media SBSE (Smart Board For Sex Education) Untuk Pendidikan Seks Anak Usia 5-6 Tahun Di TK Negeri Al-Irsyad Panta Sumatera Barat - Sri Wahyuni Fadli; Daviq Chairilsyah; Enda Puspitasari (Innovative: Journal Of Social Science Research, 2023)
his study aims to develop SBSE (Smart Board For Sex Education) media to introduce sex education to children aged 5-6 years. The type of research used is research and development (Research and Development). The steps taken are potential and problems, data/information collection, product design, product design validation, design revision, product manufacture, and product trials. Data collection techniques by observation, distributing questionnaires, and analysis of documentation. The instrument used was a questionnaire for SBSE media validation from media experts, material experts, and educators. The data analysis technique used is a quantitative descriptive analysis technique. In the study, it was obtained that the material expert validation was 82.69% "very feasible", the media expert validation was 83.13% "very feasible", educator validation results obtained a percentage of 92.63% "very feasible". The results of the limited trials conducted obtained a percentage of 90.74%. From the results of the study it was concluded that the SBSE (Smart Board For Sex Education) media is suitable for use as a learning medium in sex education for children aged 5-6 years at AL-Irsyad Panta State Kindergarten.